2006
DOI: 10.1080/02713680600865052
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic Profile of Uveal Melanoma

Abstract: Uveal melanoma develops in one of the most capillary-rich tissues of the body and is disseminated hematogenously. Knowledge of the nature and the spatiotemporal expression of angiogenic factors in uveal melanoma is essential to the development of new treatment strategies, especially with regard to improving survival. In this study, we measured the angiogenic potential of several angiogenic factors in different uveal melanoma cell lines, in an in vivo model, and in primary tumor material from patients with mela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…[25][26][27][28] As reported in the literature, uveal melanoma cell lines are known to express VEGF and basic FGF to various extents. [10][11][12]14,15 Ijland et al 12 found human uveal melanoma cell lines to express also PDGF. Vascular endothelial growth factor itself was increased in the aqueous humor of eyes with uveal melanoma.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…[25][26][27][28] As reported in the literature, uveal melanoma cell lines are known to express VEGF and basic FGF to various extents. [10][11][12]14,15 Ijland et al 12 found human uveal melanoma cell lines to express also PDGF. Vascular endothelial growth factor itself was increased in the aqueous humor of eyes with uveal melanoma.…”
Section: Discussionmentioning
confidence: 98%
“…[5][6][7][8][9] So far VEGF, FGF, and a number of inflammatory cytokines have been described in aqueous samples of uveal melanoma. [10][11][12][13][14][15] However, to this date, this is the only work describing cytokine levels in the vitreous fluid of eyes with uveal melanoma in detail.…”
mentioning
confidence: 93%
“…Uveal melanomas are also observed in human patients. The mostly used murine uveal melanoma model relies on injection of uveal melanoma cells of murine or human origin into the eye, thus allowing to monitor maintenance and progression, but not initial development of the tumor (Notting et al, 2006;Yang et al, 2008). In addition, there is a transgenic murine model for pigmented ocular neoplasm, in which large T antigen, driven by the Tyrp promoter, is causative for the disease (De la Houssaye et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Uveal melanoma cells have been shown to produce a variety of factors, which modify angiogenesis and the tumor stroma [27,30,31]. The ability of imatinib mesylate to reduce the production of proangiogenic factors such as VEGF has been implicated in its antitumor activity in other malignancies, such as neuroblastoma and lung Groups of six mice were treated with PBS, with 150 mg/kg temozolomide (TMZ) on days 9 and 10, with 1 mg/mouse/day imatinib mesylate (IM) days 6-9, or with IM days 6-9 and TMZ on days 9 and 10 (IM + TMZ).…”
Section: Discussionmentioning
confidence: 99%